SOCIAL DIMENSION OF SMOKING WITHIN YOUNG POPULATION - R. Pejchinovska; I. Brchina; G. Pejchinovski; P. Malinska; Sh. Musa; V. Dobrosavljevikj; Lj. Kostadinovski; M. Gjetaj Jakovski; P. Simjanoski (Македонско лекарско друштво = Macedonian Medical Association, 2017)
Introduction According to the Strategy for Tobacco Control in order to provide and improve health protection of the population of the Republic of Macedonia, and a number of international documents, basic strategic directions are that the health is the most important investment in the social and economic development of the community, and epidemic of smoking presents an increasing threat to people’s health. It is considered that there are 1.3 billion smokers worldwide, and current projections of the WHO show that this number will rise to 1.7 billion smokers by 2025, if the global prevention of tobacco use remains unchanged. Objectives The goal of this research is to determine the knowledge and views of the young people in the Republic of Macedonia concerning the use of tobacco, its influence on the social environment as a certain socio-pathological phenomenon or risk factor for certain diseases of the people. Materials and Methods The survey was conducted in the following municipalities in the Republic of Macedonia: Centar, Karpos, Gazi Baba, Kisela Voda, Cair, Aerodrom, Gorce Petrov and Butel in the city of Skopje, then municipalities Prilep, Kumanovo, Struga and Gostivar. Random sample. Target groups: young people at the age from 15 to 22. Research tools: a survey questionnaire no. 1. Subjects from sample were divided into 2 groups: subjects who smoked and those who did not smoke. Following statistical tests were applied: Pearson Chi-square, Kolmogorov-Smirnov, Kruskal-Wallis ANOVA, Mann-Whitney, Spearmanov Rank Correlations, Pearson-ov koeficient na korelacija. Results Boys smoke significantly more than girls (X2= 13.3 df=1 p<0.0003). Among students smokers are significantly dominant (56.71%). Ethnic background of the young smokers/non-smokers corresponds with the population structure. Young people try their first cigarette at the age of 14-16 (r = .12744). Young people smoke everywhere (Dmax = 0.11 p>0.05). Young people smoke every day (86.59%). Young people usually smoke 5-10 cigarettes a day and they buy them at the news-stands. Young people in the R.M. rarely do sports (only 34.15%). Young people at the age of 15-20 usually smoke while they listen to music, while young people at the age of 21-22 usually smoke while they watch TV. More than half of the subjects think that the community they live in is a good place for living. Reasons for smoking are: habit, family problems, love problems, school, peer pressure, etc. There are no significant differences with regard to this question in municipalities. Conclusion In general, young people in Macedonia think that their peers who smoke are not well accepted by the community. Young people in Republic of Macedonia are well informed on smoking as a social-pathological phenomenon, and also that smoking is a risk factor for certain diseases.
Keywords: smoking; young people; legislation